2017
DOI: 10.1016/j.bpj.2016.11.259
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of Cellular Co-Translational Folding Indicates Proteins can Switch from Post- to Co-Translational Folding

Abstract: The rates at which domains fold and codons are translated are important factors in determining whether a nascent protein will co-translationally fold and function or misfold and malfunction. Here we develop a chemical kinetic model that calculates a protein domain's co-translational folding curve during synthesis using only the domain's bulk folding and unfolding rates and codon translation rates. We show that this model accurately predicts the course of co-translational folding measured in vivo for four diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…For example, it was suggested that translation elongation is lower downstream of the protein domain boundaries probably to improve the fidelity of co-translational domain-wise protein folding (57,66). Similar ideas related to elongation and co-translational folding have been suggested based on additional techniques including the tAI and TASEP based models (98,169). …”
Section: Introductionmentioning
confidence: 80%
“…For example, it was suggested that translation elongation is lower downstream of the protein domain boundaries probably to improve the fidelity of co-translational domain-wise protein folding (57,66). Similar ideas related to elongation and co-translational folding have been suggested based on additional techniques including the tAI and TASEP based models (98,169). …”
Section: Introductionmentioning
confidence: 80%
“…In some cases, these changes are associated with diseases . Synonymous mutations that change elongation rates can even switch folding of some protein domains from post‐translational to cotranslational . Alterations in codon context caused by synonymous mutations may also induce the mis‐incorporation of amino acids, leading to protein misfolding …”
Section: Elongation Processivity and Protein Foldingmentioning
confidence: 99%
“…There is evidence of computational analysis that fast translation speed can increase the probability of cotranslational protein folding. [75][76][77] It is now important to consider the coding sequence while performing protein folding in silico. In this regard, the recently developed CSandS database is worth to consider while designing protein three-dimensional structure.…”
Section: Translation Kinetics Guides Cotranslational Protein Foldingmentioning
confidence: 99%